1984
DOI: 10.1093/infdis/150.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Production of Menaquinones by Intestinal Anaerobes

Abstract: Ninety intestinal organisms (71 isolates from fecal samples of neutropenic patients with cancer or from various sites in patients with intraabdominal infections and 19 control strains) were examined by reverse-phase thin-layer chromatography for their ability to produce menaquinones in vitro. Menaquinones were found in all of 24 organisms of the Bacteroides fragilis group. Two other Bacteroides species, Bacteroides disiens and Bacteroides bivius, also produced menaquinones. A single isolate of Bacteroides spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(77 citation statements)
references
References 30 publications
5
72
0
Order By: Relevance
“…Vitamin B 12 is an exclusive product of prokaryotes (98), and it is produced by plant root and gut bacteria (99)(100)(101)(102). Essential amino acids and vitamins B and K are produced by gut bacteria (reviewed in reference 58).…”
Section: Gut and Root Bacteria Enhance The Metabolic Capacities Of Thmentioning
confidence: 99%
“…Vitamin B 12 is an exclusive product of prokaryotes (98), and it is produced by plant root and gut bacteria (99)(100)(101)(102). Essential amino acids and vitamins B and K are produced by gut bacteria (reviewed in reference 58).…”
Section: Gut and Root Bacteria Enhance The Metabolic Capacities Of Thmentioning
confidence: 99%
“…The microbial cells inside the human gastrointestinal (GI) tract are collectively called the GI microbiota and provide an extensive genetic function counterpart to the host genome (Savage, 1977;Albert et al, 1980;Adlercreutz et al, 1984;Ramotar et al, 1984;Cummings and Macfarlane, 1997;Cebra, 1999;Metges, 2000;Shanahan 2002;Begley et al, 2005;O'Hara et al, 2006;Wei and Brent, 2006;Yang et al, 2009). Previous studies have shown that GI microbiota is host-specific and GI tract region-specific (Zoetendal et al, 2004;Rajilic-Stojanovic et al, 2009;Jalanka-Tuovinen et al, 2011), aberrant in composition and stability in patients suffering from GI disorders such as Crohn's disease (Seksik et al, 2003), and associated to host energy homeostasis (Backhed et al, 2004;Ley et al, 2006;Turnbaugh et al, 2006;Backhed et al, 2007;Samuel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The search for a regimen which would be successful yet nontoxic has yielded several cephalosporins. When introduced, moxalactam appeared to be effective in this niche; however, it is not active against many strains of P. aeruginosa and is associated with prolongation of PT in some patients (2,4,12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime is a promising cephalosporin with excellent in vitro activity against many such strains (3,16). Furthermore, therapy with ceftazidime has not been associated with bleeding and prolongation of prothrombin time (PT), as has occurred with moxalactam (2,4,12,15).…”
mentioning
confidence: 99%